Pengaruh Perkembangan Kehidupan Masyarakat terhadap Pengaturan Hukum tentang Aborsi di Indonesia - Paulinus Soge (Fakultas Hukum Universitas Islam Indonesia, 2000)
The purpose of this article is neither to explore the evolution of US Supreme Court doctrine concerning abortion, nor to discuss about the controversy on abortion issue occurred at The International Conference on Population and Development (ICPD) in Cairo in September 1994. The discussion is directed to the area of legal policy to anticipate a legal change on abortion in Indonesian Penal Law from